The impact of ultraviolet radiation on the skin and the role of photoprotection – the review of the literature - Antonik, Dominika; Denys, Barbara; Góra, Karolina; Zdziennicki, Wojciech; Zimnicki, Patryk; Lato, Marta; Iberszer, Konrad; Litwiniuk, Maria; Zaniuk, Marcin; Hurkała, Kamil (Journal of Education, Health and Sport, 2023)
Introduction and objective: The sun emits ultraviolet radiation in the UV-A, UV-B and UV-C ranges. Photoprotection is used to prevent the impact of this radiation on the skin. It effectively counteracts photoaging, photodermatoses and photocarcinogenesis. The aim of the study is to discuss the impact of UV radiation on the skin and the role of sun protection, also in special groups of patients - children and non-immunocompetent people. The article also presents a summary of data on the effect of sunscreens on vitamin D synthesis. Materials and methods: The literature was reviewed in the Pubmed, Google Scholar database and in the recommendations of the Polish Dermatological Society with the use of keywords. State of knowledge: Erythema is the most visible effect of sunburn, but exposure to UV radiation is primarily photocarcinogenesis or photoimmunosuppression. The SPF factor is the main determinant of the effectiveness of sunscreens, but effective protection against both UVB and UVA radiation is essential. Daily use of sunscreen reduces skin damage associated with exposure to light and does not negatively affect vitamin D synthesis. Conclusions: The basis of skin protection is using sunscreens, avoiding excessive exposure to solar radiation and using protective clothing, hats and sunglasses. Thanks to these activities, we can significantly reduce the number of cases of certain skin cancers. It is also important to remember that sun protection applies to everyone, especially children and non-immunocompetent people.